Familial amyloidotic polyneuropathy: current and emerging treatment options for transthyretin-mediated amyloidosis - Hund, Ernst (The application of clinical genetics, 2012)
Familial amyloidotic polyneuropathy: current and emerging treatment options for transthyretin-mediated amyloidosis Ernst HundDepartment of Neurology, University of Heidelberg, Heidelberg, GermanyAbstract: Transthyretin familial amyloid polyneuropathy (TTR-FAP) is a fatal clinical disorder characterized by extracellular deposition of abnormal fibrils derived from misfolded, normally soluble transthyretin (TTR) molecules. The disease is most commonly caused by a point mutation within the TTR gene inherited in an autosomal dominant fashion. Over 100 of such mutations have been identified, leading to destabilization of the physiological TTR tetramer. As a result, many monomers originate with a tendency for spontaneous conformational changes and self-aggregation. The main clinical feature of TTR-FAP is progressive sensorimotor and autonomic neuropathy. In the beginning, this polyneuropathy predominantly involves small unmyelinated nerve fibers with the result of dissociated sensory loss disproportionately affecting sensation of pain and temperature. Autonomic neuropathy typically accompanies sensory deficits early in the disease course. The symptoms include orthostatic hypotension, constipation alternating with diarrhea, erectile dysfunction, anhydrosis, and urinary retention or incontinence. Later, involvement of motor fibers causes rapidly progressive weakness and gait disturbances. In addition to the peripheral nervous system, the heart and the gut are frequently affected. Onset of symptoms is bimodal, with one peak at age 33 years (early onset) and another distinct peak in the sixth decade of life (late onset). The course of TTR-FAP is uniformly progressive and fatal. Death occurs an average of 10.8 years after the onset of symptoms in Portuguese patients, and 7.3 years in late-onset Japanese patients. Common causes include cachexia, cardiac failure, arrhythmia, and secondary infections. Liver transplantation is the standard therapy for patients who are in a clinical condition good enough to tolerate this intervention because it stops progression of neuropathy by removing the main source of mutant TTR. Recently, orally administered tafamidis meglumine has been approved by European authorities for treatment of FAP. The substance has been shown to stabilize the TTR tetramer, thereby improving the outcome of patients with TTR-FAP. Various other strategies have been studied in vitro to prevent TTR amyloidosis, including gene therapy, immunization, dissolution of TTR aggregates, and free radical scavengers, but none of them is ready for clinical use so far.Keywords: FAP, transthyretin, amyloidosis, treatment, therapy
Gesehen am 15.11.2018